Fuel Cell Based Ultra-Voltage Gain Boost Converter for Electric Vehicle Applications (2023)
The proposed fuel cell-based ultra-voltage gain boost converter offers an alternative to transformer-based topologies for achieving high voltage gain. While transformers can achieve high voltage gains, they come with drawbacks such as high cost, design complexity, and increased weight. In this article, a switched inductor circuit is introduced as an alternative solution to achieve high voltage gain. This circuit enhances overall system performance by reducing size, weight, and cost. Operating in a transformer-less topology, the converter boosts voltage levels while ensuring low voltage stress on the switching devices. The suggested design enables larger voltage gain values even at low duty ratios. The output of the fundamental boost converter serves as the input for the switched inductor circuit, effectively boosting the voltage level and supplying more voltage to the output side. This converter is particularly suitable for applications requiring ultra-voltage gain in electric vehicles, which offer reduced pollution compared to internal combustion engines. Moreover, the utilization of this topology reduces space requirements. The article presents a thorough investigation of the steady state operation in continuous conduction mode, and theoretical verification and MATLAB simulations demonstrate the performance and operation of the proposed converter.